ERP Responses of Elementary-Age Children to Video Game Simulations of Two Stimuli Types: Study 1 and 2 Comparisons. Issue 1 (2nd January 2017) - Bergen, Doris; Schroer, Joseph E.; Thomas, Robin; Zhang, Xinge; Chou, Michael; Chou, Tricia
ABSTRACT: The hypothesis that brain activity may differ during varied types of video game play was investigated in two studies of event-related potentials exhibited by children age 7 to 12 when processing game-based stimuli requiring correct/incorrect responses or choices between two imaginative alternative responses. The first study had 22 children of families from the university community and the second (replication) study had 22 children from a diverse group of community families. These participants also were interviewed regarding the children's video game habits. In Study 1, mean amplitude of P300 in the two conditions showed significant differences at P100 and N200 locations. Study 2 results showed greater N200 and P300 positive amplitude in the choice condition at Pz. Both studies found significant frontal lobe interaction for younger children in mixed conditions, suggesting they put more attention resources into the mixed task. Implications of video game play effects on brain development during the elementary years are discussed.